Pain Scales in Research (Advancements in Homeopathic Research, 2023)
In today’s era there are different types of scales to  assess a particular disease condition. Also going  through the process of research for the very first  time might be quite cumbersome. The reliability  and validity of the scale is an essential aspect in  any research study. Also thorough knowledge and  understanding of every scale is important for its  productive application.
Keywords: Research; sensitivity; validity; intraclass correlation